Willingness to Pay for Breast Cancer Screening: A Systematic Review - Ramadhani, Anietta Indri; Kristina, Susi Ari; Trung, Vo Quang (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: Women's breast cancer was identified as the primary contributor to global cancer cases. This condition puts a significant economic burden on both society and the healthcare system, with the highest expenses related to medical treatment costs.Objectives: The study aims to review the willingness to pay (WTP) for breast cancer screening and the factors influencing it.Methods: Four databases (Scopus, PubMed, ProQuest, and Google Scholar) were used to search related articles that mentioned the WTP for breast cancer screening. Preferred Reporting Items for Systematic Reviews (PRISMA) guideline was used to execute this systematic review study. Finally, 11 articles were included in this study. The quality of reviewed studies was assessed using a JBI cross-sectional study and a JBI quasi-experimental study.Results: The study found that the WTP value for breast cancer screening varied from $1 to $500 in Iran, Malaysia, Singapore, the US, and Canada. Most studies explained that willingness to pay and willingness to take breast cancer screening were affected by sociodemographic aspects such as family history of ovarian or breast cancer, income status, education status, age, and marital status.Conclusion: Governmental authorities should consider the implementation of a breast cancer screening program or explore cost-sharing mechanisms for breast screening, to mitigate the incidence of breast cancer.